Voltage-dependent gating of SV channel TPC1 confers vacuole excitability - Dawid Jaślan (Nature Portfolio, 2019)
Electrical excitability in animals and plants is associated with voltage-gated Shaker-type K+ channels at the plasma membrane. Here, Jaślan et al. show that electrical excitability of the central organelle of plant cells, the vacuole, is based on the action of Ca2+-activated and K+-conducting TPC1 and TPK channels.